Fascism and political theory critical perspectives on fascist ideology - Woodley, Daniel. (Routledge issues in contemporary political theory, 2010)
The textöffers both students and researchers a thematic analysis of fascism, focusing on the structural and ideological links between fascism, capitalism and modernity. Intended as a critical discussion of the origins and development of fascist ideology, each chapter deals with a core substantive issue in political theory relevant to the study of fascism and totalitarianism, beginning with an assessment of the current state of debate.